1979
DOI: 10.1111/j.1365-2621.1979.tb09099.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature Air Oven vs a Water Bath for the Preparation of Rare Beef

Abstract: Paired muscles were used to assess the merits of a water bath method for the preparation of rare beef as compared to a conventional oven using a long-time, low-temperature process. Samples prepared in a water bath were more uniformly rare in cross-section, had significantly greater cooked yields, and were significantly more tender than oven-cooked roasts. A sensory panel found water bath samples to be significantly more tender and preferred them overall to oven-cooked samples. In addition to the above advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Although the enthalpy value of wet air (steam) is higher, and more energy can be transferred to the sample than dry air and water, heat transfer can be enhanced by the forced circulation of water or by higher cooking temperature of the dry air. Buck et al (1979) and Burfoot et al (1990) both found that water bath could reach higher rate of heat penetration even with cooking bag at the lower bath temperature, so all the above results could be obtained. After cooking, the traditional air blast cooling was used to cool the ham from 72 to 4°C.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Although the enthalpy value of wet air (steam) is higher, and more energy can be transferred to the sample than dry air and water, heat transfer can be enhanced by the forced circulation of water or by higher cooking temperature of the dry air. Buck et al (1979) and Burfoot et al (1990) both found that water bath could reach higher rate of heat penetration even with cooking bag at the lower bath temperature, so all the above results could be obtained. After cooking, the traditional air blast cooling was used to cool the ham from 72 to 4°C.…”
Section: Resultsmentioning
confidence: 62%
“…Much evidence suggests that water cooking has many potential advantages to cook meat, such as increasing the tenderness and yield, improving the microbiological safety through high efficient heat penetration, and controlling the preciseness of degree of doneness and reducing energy cost (Buck, Hickey, & Rosenau, 1979;Cyril, Castellini, & Dal Bosco, 1996). Although water cooking has wide application in meat research, literature related to its industrial application are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, few publications dealt with the storage stability of these products (Church & Parsons, 1993; Hansen et al ., 1995). However, a number of investigations about technological characteristics, sensory quality and shelf‐life stability of s ous vide and vacuum cook‐in bag meat have been published (Buck et al ., 1979; Dinardo et al ., 1984; Smith & Alvarez, 1988; Stites et al ., 1989; Cooksey et al ., 1990; Hansen et al ., 1995; Bertelsen & Juncher, 1996; Church, 1996; Thorsell, 1996; Palka & Daun, 1999; Vaudagna et al ., 1999; Church & Parsons, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Cia and Marsh (1976) found that microwave cooking improved the tenderness of prerigor muscle compared to boiling, whereas Montgomery et al (1977) reported that conventional roasting produced greater tenderness than microwave cooking. Buck et al (1979) found that roasts cooked in a water bath postrigor were more tender than paired roasts cooked by oven roasting.…”
Section: Resultsmentioning
confidence: 97%